Piezo1 Affects Temporomandibular Joint Osteoarthritis by Influencing pSmad3 - Wu, Chuan-Bin; Ma, Tie; Ma, Lin; Wang, Qiang; Zhou, Qing (Frontiers in Physiology, 2022)
Objective: The aim of this research was to study the expression of Piezo1 in a rat temporomandibular joint osteoarthritis animal model and to explore its mechanism for inducing inflammatory changes. Methods: A total of 24male SD rats aged approximately 8 weeks were randomly divided into three groups: the blank control group, complete Freund’s adjuvant group (CFA), and CFA + inhibitor (GsMTx4) group. After 3 weeks, the condylar heads of the rats were evaluated by micro-CT, HE, immunohistochemistry, safranin O staining, and other experimental techniques. Protein was extracted from the subchondral bone, and the changes in Piezo1, Smad3, and pSmad3 levels in each group were detected by Western blotting. p < 0.05 was considered to indicate statistical significance. Results: The degree of damage to the cartilage and subchondral bone in the Piezo1 inhibitor group was smaller than that in the CFA group. The expression level of Piezo1 in the CFA group was higher than that in the other groups, and the difference was statistically significant. The expression of pSmad3 in the CFA group was also higher than that in the other groups (p < 0.05). Conclusion: Piezo1 is expressed in the condylar cartilage and subchondral bone of rats, and the degree of condylar destruction can be improved by influencing the pSmad3 expression.